Encapsulation protective effect upon viability of probiotic bacteria throughout storage and gastrointestinal tract - Rodrigues, D. (2010)
Microcapsules (MC) with fresh cultures of potential probiotic strains (Lactobacillus paracasei LAFTI® L26, L. acidophilus Ki and Bifidobacterium animalisBB-12®) were produced by spray-drying using whey protein concentrate (WPC50) with or without L-cysteine (0.5 g/L). After microencapsulation, the MC were stored, in duplicate, at 5ºC over a period of 6 months during which the number of viable cells (VC) were evaluated. After 15, 60 and 120 days of storage, their resistance throughout gastrointestinal conditions was evaluated. In MC without L-cysteine, the VC numbers of L. acidophilus Ki and B. animalis BB-12® after 6 months of storage decreased from 108 to 106 cfu/g whereas no decrease was observed for L. paracasei. The presence of L-cysteine revealed a positive effect, especially for L. acidophilus Ki after 90 days of storage accounting for more than one logarithm cycle increase in viability. Encapsulation had a protective effect on the three probiotic strains when exposed to the gastrointestinal conditions in comparison to their free cells. This effect was particularly significant for L. acidophilus Ki in conditions similar to those of ileum/duodenum including the presence of pancreatin and bile salts. Storage time did not affect the resistance of the three probiotic strains to the gastrointestinal conditions.